The role of cancer-associated fibroblasts in the invasion and metastasis of colorectal cancer - Yin, Jinjin; Zhu, Wenting; Feng, Senling; Yan, Pengke; Qin, Shumin (Frontiers in Cell and Developmental Biology, 2024)
Colorectal cancer (CRC) is the third most common cancer and has ranked the third leading cause in cancerassociated death globally. Metastasis is the leading cause of death in colorectal cancer patients. The role of tumor microenvironment (TME) in colorectal cancer metastasis has received increasing attention. As the most abundant cell type in the TME of solid tumors, cancer-associated fibroblasts (CAFs) have been demonstrated to have multiple functions in advancing tumor growth and metastasis. They can remodel the extracellular matrix (ECM) architecture, promote epithelial-mesenchymal transition (EMT), and interact with cancer cells or other stromal cells by secreting growth factors, cytokines, chemokines, and exosomes, facilitating tumor cell invasion into TME and contributing to distant metastasis. This article aims to analyze the sources and heterogeneity of CAFs in CRC, as well as their role in invasion and metastasis, in order to provide new insights into the metastasis mechanism of CRC and its clinical applications.